ANALISIS PENGARUH FAKTOR SOSIAL DEMOGRAFI DAN AKTIVITAS EKONOMI TERHADAP KESEJAHTERAAN KELUARGAPEMULUNG DI KOTA DENPASAR - Putri Wiyatna, Made Yustisa; Utama, Made Suyana; Marhaeni, A.A. I.N (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.04.TAHUN 2015, 2015)
ABSTRACT Scavangers are often categorized as non-elite and marginal occupation in society. However, it’s still chosen by people as their main job. This phenomenon start to increases every year not only in the big city but also in second-largest city especially Denpasar. This research has several purpose, as following: identify scavenger’s walfare rate, get differencies between male and female scavenger, analyse socio-demography and activity impact on its walfare, and analyse indirect effects of socio-demography on it’s walfare especially in Denpasar City. The primary data were obtained by doing direct interviews and giving questioners to 100 scavangers in Denpasar City. The secondary data were obtained from Department of Public Works Bali and Department of Cleanliness and Landscaping Denpasar. The sampling technique that is used in this research is non-probability sampling with accidental sampling. The data were analysed using descriptive and PLS analysis. The results show that scavengers are dominated by male whose age between 30-49 years old. Most of them are married (21-30 years of marriage) and have two childs.  Furthermore, most of them also are migrant who live in Denpasar less than 5 years and have unfinished primary school background. Scavangers mostly use less than Rp 500.000,- to travel between 61 – 175 metres in 41-60 hours. By receiving an income less than Rp 1.000.000,- , they assume that they can cover their family living cost.  Moreover, this research reveals that there is a difference between male and female in case of the income. It also finds that socio-demography and economy activities have positive significant impacts on scavenger life. In addition, economy activities have a significant impact on connecting the socio-demography to scavenger welfare in Denpasar. Therefore, some health socialisation and creativity workshops are worth to be done to increase the scavenger’s welfare rate.
Keywords: Social Demography, Economy Activities, Welfare, Scavenger